Trust Exercise by Susan Choi: An annotated translation - Aprodhita Galuh Karima; Malikhatul Lailiyah (Universitas Merdeka Malang, 2023)
This study presents an analysis of annotated translations focusing on the novel â€œTrust Exerciseâ€ by Susan Choi, published in 2019. The objective of this study is to identify suitable translation strategies for effectively translating cultural-specific terms encountered in Choiâ€™s novel. Specifically, the annotations in this report pertain to Part 1 of the novel. The researchers identifies eight translation problems encountered in this section, the first being comprehension of the source text, including words, phrases, clauses, and sentences. To address these challenges, the researchers employed a simultaneous understanding and transferring approach, utilizing online dictionaries as translation aids. Moreover, the researchers adopted the most suitable translation strategy to enhance text comprehensibility. Semantic strategies were predominantly employed by the researchers, considering meaning at various linguistic levels, including words, phrases, clauses, and sentences.